Spontaneous Abdominal Wall Hematoma Following Violent Cough: A Rare but Severe Condition—Surgical Challenges and Outcomes Regarding Three Cases and a Literature Review - Claudiu Octavian Ungureanu; Floris Cristian Stănculea; Alexandru Iordache; Cosmin Burleanu; Valentin Titus Grigorean; Octav Ginghina; Mircea Lițescu (Reports)
Background and Clinical Significance: Spontaneous abdominal wall hematoma following violent coughing is a rare condition that poses a sometimes difficult therapeutic challenge, with surgical intervention often necessary in severe cases. This report aims to shed light on this rare but severe affection and raise the medical community’s interest by detailing the pathophysiology, management strategies, and outcome of spontaneous abdominal wall hematoma. Case Presentation: The basis for our paper was a comprehensive retrospective analysis of three cases treated in our surgical departments. We rigorously reviewed their clinical notes and imaging examinations to ensure the accuracy and reliability of our findings. Conclusions: These case reports underscore the challenging nature of such hematomas. Clinicians should be aware of this pathology, as it can be life-threatening. Our successful management of these cases shows that it is possible to effectively manage difficult clinical situations with timely intervention.